2016
DOI: 10.1097/j.pain.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed connectivity of the amygdala and its subregions with the central executive and default mode networks in chronic pain

Abstract: Maladaptive responses to pain-related distress, such as pain catastrophizing, amplify the impairments associated with chronic pain. Many of these aspects of chronic pain are similar to affective distress in clinical anxiety disorders. In light of the role of the amygdala in pain and affective distress, disruption of amygdalar functional connectivity in anxiety states, and its implication in the response to noxious stimuli, we investigated amygdala functional connectivity in 17 patients with chronic low back pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 60 publications
5
89
1
1
Order By: Relevance
“…Both human and animal studies have demonstrated that stress hormones modify BDNF expression, such that there is decreased BDNF expression in the hippocampus and increased expression in the amygdala [94,95,96]. This finding is consistent with recent neuroimaging studies, which have reported significant loss in hippocampal neuroconnectivity with the medial prefrontal cortex [97], and exaggerated amygdalar connectivity with the central executive network (dorsolateral prefrontal cortex and posterior parietal cortex) in individuals with chronic pain compared to healthy controls [98]. Therefore, genetically determined BDNF availability may modify brain connections contributing to the development and maintenance of chronic pain conditions.…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid supporting
confidence: 84%
See 2 more Smart Citations
“…Both human and animal studies have demonstrated that stress hormones modify BDNF expression, such that there is decreased BDNF expression in the hippocampus and increased expression in the amygdala [94,95,96]. This finding is consistent with recent neuroimaging studies, which have reported significant loss in hippocampal neuroconnectivity with the medial prefrontal cortex [97], and exaggerated amygdalar connectivity with the central executive network (dorsolateral prefrontal cortex and posterior parietal cortex) in individuals with chronic pain compared to healthy controls [98]. Therefore, genetically determined BDNF availability may modify brain connections contributing to the development and maintenance of chronic pain conditions.…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid supporting
confidence: 84%
“…Baliki et al [154] also noted over the same time course that gray matter brain density decreased in patients with low back pain relative to healthy controls. However, adult chronic low back pain patients also tended to have exaggerated amygdalar connectivity with the central executive network (dorsolateral prefrontal cortex and posterior parietal cortex) as compared to healthy controls [98]. Moreover, this greater connectivity has been associated with increased tendencies to engage in catastrophic thinking about pain [98].…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid mentioning
confidence: 99%
See 1 more Smart Citation
“…While it is unknown whether structural deficits were antecedents or consequences of catastrophizing, their co-occurrence suggests a mutually-reinforcing biobehavioral cycle of pain and potential nocebo-induced hyperalgesia (Blasini, Corsi, Klinger, & Colloca, 2017). Indeed, pain catastrophizing in individuals with chronic pain has been shown to associate with altered neural functioning outside of the context of evoked pain or in vivo catastrophizing (Jiang et al, 2016). Greater pain catastrophizing is associated with altered brain functioning in the default mode network—an over-coupling between the central executive network and the amygdala—that attune the brain to pain (Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pain catastrophizing in individuals with chronic pain has been shown to associate with altered neural functioning outside of the context of evoked pain or in vivo catastrophizing (Jiang et al, 2016). Greater pain catastrophizing is associated with altered brain functioning in the default mode network—an over-coupling between the central executive network and the amygdala—that attune the brain to pain (Jiang et al, 2016). These findings suggest that pain catastrophizing is associated with neural alterations in individuals with chronic pain that appear to prime their nervous pain signaling systems for future pain.…”
Section: Introductionmentioning
confidence: 99%